Democratisation, Decentralisation and Islam: A Reflection of Two Decades of Indonesia's Local Autonomy - Mukrimin Mukrimin; Lahaji Lahaji; Andi Akifah (Al-Ulum, 2018)
In Indonesia, decentralisation has emerged in the name of democratisation over the last decades. Decentralisation, politically, has significantly shaped the relationship between the central and local governments. Therefore, many have believed that the decentralisation is equivalent to the democratisation process. In this article, we attempt to answer these questions: (1) is the decentralisation compatible with consolidated democratisation in Indonesia? (2) How is â€œthe rule by peopleâ€ implemented for the sake of democracy; in other words, how local people fill these spaces? In this article, we argue that there has been a connection between democratisation process and decentralisation. However, the relationship seems to be superficial.